The Effect Of Stress On The Level Of Dysmenorrhea In Young Women - Noviyanti, Asri; Jasmi, Jasmi (Journal of Maternal and Child Health Sciences (JMCHS), 2023)
Menstruation is one of the characteristics that indicate that a woman is entering puberty. During menstruation there is discomfort in a woman's physique, namely dysmenorrhea. This study uses a correlation analytic research design with a cross sectional approach. The sample of this study were young women who had experienced menstruation. The inclusion criteria were that young women had experienced menstruation for at least 1 year. This study used a purposive sampling technique with a total sample of 92 respondents. The research instrument used was the DASS questionnaire sheet to assess the stress scale and the numeric rating scale (NRS) to measure the level of adolescent dysmenorrhea. Data analysis consisted of univariate and bivariate analysis. In the bivariate analysis, the relationship between the two variables was sought by using the Spearman test. The results showed that most of the respondents experienced normal stress levels, namely 68 respondents (73.9%), most of the respondents experienced mild pain, namely as many as 38 respondents (41.3) and there was a significant relationship between stress and dysmenorrhea with p = 0.000 ( r=0.345). At times of stress the body will produce the production of the hormones estrogen, progesterone, adrenaline and also prostaglandins increase, increased secretion of f2 alpha prostaglandins causes an increase in the frequency of uterine contractions, causing vasospasm and ischemia in the uterine arteries. The ischemic response that occurs in this condition causes pain in the lumbar region, weakness, edema, diaphoresis, anorexia, nausea, vomiting, diarrhea, headaches, decreased concentration, emotional lability and other symptoms